Symmetry and asymmetry in property: Commons and anticommons - Francesco Parisi; Norbert Schulz; Ben Depoorter (University of Würzburg, Department of Economics, 2003)
Commons and Anticommons problems are the consequence of symmetric structural departures from a unified conception of property. In this paper, we endeavor to provide a dual model of property, where commons and anticommons problems are the consequence of a lack of conformity between use and exclusion rights. While Commons and Anticommons problems are symmetric in this sense, they are associated with asymmetric transaction costs. The paper formulates a hypothesis of legal rules for promoting unity in property and suggests a list of possible areas of application.
Keywords: 330; Allmenderessource; Eigentumsrecht; Theorie